Agama Yahudi sebagai Fakta Sejarah dan Sosial Keagamaan - Ilim Abdul Halim (UIN Sunan Gunung Djati Bandung, 2017)
Some the term in literature english used to mention jews were; hebrew / hebron ( hebrew ), israelites ( orang-orang israel ), children of ismael ( anak-anak ismael ), judeans ( orang-orang judah ) and jews ( orang-orang jewish). Jews can in terms of two sides : ethnic and religion. On one side were as an ethnic has played a variety of historical circumstances important in the dynamics of his life to be a record world history. A jewish religious sociological including having religious unsur-unsur the religious beliefs, religious experience, religious rituals and religious communities.